Bluelizardite, Na7(UO2)(SO4)4Cl(H2O)2, a new uranyl sulfate mineral from the Blue Lizard mine, San Juan County, Utah, USA - Plasil,J.; Kampf,A.R.; Kasatkin,A.V.; Marty,J. (Journal of Geosciences, 2014)
Bluelizardite (IMA 2013-062), Na7(UO2)(SO4)4Cl(H2O)2, is a new uranyl sulfate mineral from the Blue Lizard mine, San Juan County, Utah (USA). It was found in a sandstone matrix and is associated with chalcanthite, copiapite, ferrinatrite, gypsum, kröhnkite, johannite, and several other new, unnamed Na- and Mg-containing uranyl sulfates. Bluelizardite is a supergene mineral formed by the post-mining weathering of uraninite. The mineral is monoclinic, C2/c, with a = 21.1507(6), b = 5.3469(12), c = 34.6711(9) Å, β = 104.913(3)°, V = 3788.91(17) Å3 and Z = 8. Crystals are blades up to 0.4 mm long, flattened on {001}, elongated parallel to [010] and exhibiting the forms {100}, {001} and {111}. Bluelizardite is pale yellow and has a yellowish white streak. It has good cleavage on {001} and uneven fracture. The Mohs hardness is estimated at 2. The calculated density based on the empirical formula is 3.116 g/cm3. Bluelizardite exhibits bright yellow-green fluorescence under both long- and short-wave UV radiation. The mineral is optically biaxial (-), with α = 1.515(1), β = 1.540(1) and γ = 1.545(1) (measured with white light). The measured 2V is 48(2)° and the calculated 2V is 47.6°. Mineral does not exhibit any dispersion or pleochroism. The optical orientation is X = b, Y = a, Z = c*. The empirical formula of bluelizardite is Na6.94(U1.02O2)(SO4)4.00Cl0.94O0.06(H2O)2 (based on 21 anions pfu). The Raman spectrum is dominated by the symmetric stretching vibrations of the uranyl (UO22+) group and sulfate tetrahedra and by the O-H stretching and bending vibrations of the H2O molecules. The eight strongest powder X-ray diffraction lines are [dobs Å(I )(hkl) ]: 17.08(52)(002), 10.31(60)(200), 5.16(100)(mult.), 4.569(22)(402,-114), 4.238(23)(-115, 310, 008), 3.484(27)(-602,-604,-2•0•10), 3.353(28)(mult.), 3.186(36)(mult.). The crystal structure of bluelizardite (R1 = 0.016 for 4268 reflections with Iobs > 3σI) is topologically unique among known structures of uranyl minerals and inorganic compounds. It is based upon clusters of uranyl pentagonal bipyramids and sulfate tetrahedra. Two uranyl pentagonal bipyramids are linked through the two vertices of SO4 groups. The remaining three vertices of each UO7 bipyramid are occupied by SO4 groups, linked monodentately. The eight independent Na+ cations are linked through the Na-O bonds along with hydrogen bonds (involving H…O and H…Cl bonds) into a 3D framework.
Keywords: bluelizardite; new mineral; uranyl sulfate; weathering; crystal structure; bond-valence